Prevalence and antimicrobial resistance phenotypes of Salmonella species recovered at various stages of broiler operations in Hathazari, Bangladesh - Ali, Ferdausi; Silvy, Tazriyan Noor; Hossain, Tanim Jabid; Uddin, Md. Kamal; Uddin, Mohammad Seraj (International journal of one health, 2021)
Background and Aim: Dissemination of multidrug-resistant (MDR) Salmonella through food chains has serious health implications, with higher rates of morbidity and mortality. Broiler meat remains a major reservoir of Salmonella contamination. The lack of proper hygiene in local broiler operations has, therefore, prompted this research into the assessment of Salmonella contamination in local shops and associated antimicrobial resistance (AMR) phenotypes. Materials and Methods: A total of 55 broiler samples including skin, meat, and swab samples from chopping and dressing sites were included in the study. The samples were collected from broiler shops in Hathazari, Bangladesh, and screened for the presence of Salmonella strains using culture-based methods. The isolates were biochemically characterized and further tested for AMR to eight common antibiotics using the disk diffusion technique. Results: Salmonella contaminations were identified in 29% (16/55) of the broiler samples. Swab samples collected from the chopping sites appeared to be contaminated in higher proportions (33%) than those collected from the dressing areas (25%). On the other hand, the skin samples (50%) were detected with a higher percentage of contamination than the meat samples (25%). All Salmonella isolates showed resistance toward at least one of the eight antibiotics used. Although none of the isolates was resistant to all antibiotics, 18.75% showed resistance to a maximum of seven antibiotics. Resistance to nalidixic acid was most prevalent (87.5%), followed by sulfamethoxazole-trimethoprim (81.25%), erythromycin (81.25%), tetracycline (75%), streptomycin (56.25%), ampicillin-clavulanic acid (50%), chloramphenicol (43.75%), and cefotaxime (18.75%). The resistance patterns of the isolates were found to be highly diverse. The most frequently observed pattern was the following: Ampicillin-clavulanic acid-sulfamethoxazole-trimethoprim-nalidixic acid-tetracycline-chloramphenicol-streptomycin-erythromycin. Conclusion: The relatively high prevalence of MDR strains in the samples underlies an urgent need for surveillance and control measures concerning hygiene and antibiotic use in local broiler operations.